2012
DOI: 10.1111/j.1365-2702.2012.04213.x
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle health promotion interventions for the nursing workforce: a systematic review

Abstract: Nurse leaders have a key role in driving recognition, spearheading commitment and development of targeted, whole-organisation programmes to promote health profile improvement for the nursing workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 87 publications
3
95
0
1
Order By: Relevance
“…In addition, health professionals of the ICUs in the sub-middle San Francisco region work more hours than the maximum limit of 44 hours per week established by the Consolidation of Labor Laws (CLT -Consolidação das Leis do Trabalho) (27) . It is a consensus that the practice of PA is directly related to health promotion and the prevention of chronic noncommunicable diseases (NCDs) such as heart disease, cancer, hypertension, diabetes mellitus and obesity (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) . The stressful routine in the ICU environment, where professionals work in a state of constant attention, living with suffering, pain and death, associated with working hours that often exceed labor laws regulations, low wages and lack of exercise can directly affect the health of these individuals, consequently affecting their QOL (3,(6)(7) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, health professionals of the ICUs in the sub-middle San Francisco region work more hours than the maximum limit of 44 hours per week established by the Consolidation of Labor Laws (CLT -Consolidação das Leis do Trabalho) (27) . It is a consensus that the practice of PA is directly related to health promotion and the prevention of chronic noncommunicable diseases (NCDs) such as heart disease, cancer, hypertension, diabetes mellitus and obesity (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) . The stressful routine in the ICU environment, where professionals work in a state of constant attention, living with suffering, pain and death, associated with working hours that often exceed labor laws regulations, low wages and lack of exercise can directly affect the health of these individuals, consequently affecting their QOL (3,(6)(7) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies, especially in the nursing area, have shown that QOL is associated with the conditions offered in these locations (4,(6)(7)(8)(9)(12)(13) and, when coupled with a sedentary lifestyle, it can influence the health-disease process. A sedentary lifestyle, along with smoking and bad eating habits are risk factors for the development or worsening of NCDs (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) . All professionals in this study had an average of over 55 hours per week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few years ago, first author would like to test the model of family health promotion development, the "concepts and its relationship of family health promotion model" consists of four dynamically in terms of weight loss or prevention of weight gain, improved diet, increased exercise and activity, smoking cessation, and reduction in hazardous alcohol consumption [22]. Subjects will be interviewed including health needs assessment, family health behaviors, family health capacity, and health status, which measurements include personal health risk factors assessment examine body structure (height/wrist ratio, body mass index, lumbar/waist ration), nutritional assessment including BMI condition, health problem crisis increase, body weight assessment compare with ideal body weight, nutrition condition (body weight/ideal body weight ratio), and health risk (lumbar/ waist ration).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it contributes to the improvement of symptoms, general well-being and quality of life. (2)(3)(4) Information about certain groups of risk factors may address the development of intervention programs. Among hypertensive subjects, for example, the prevalence of other cardiovascular risk factors are high.…”
Section: Introductionmentioning
confidence: 99%